Approximation of undrained bearing capacity of strip foundations on heterogeneous marine clay - R. Jamshidi Chenari; A. Izadi; A. Eslami; E. Khaksar Najafi (Numerical Methods in Civil Engineering)
The problem of bearing capacity of foundation under rigorous circumstances has always been of a great importance in geotechnical engineering. Various simple and also more sophisticated methods have been developed to improve the bearing capacity calculations. In this paper, the performance of three different approximate methods including the limit equilibrium analysis, upper and lower bound of the limit analysis, and the characteristic method of the slip line solution is evaluated and compared in dealing with marine soil deposits with the heterogeneous soil strength profile under the plane strain condition. The undrained bearing capacity of strip footing rested on a stratum with a linear variation of undrained shear strength was estimated using various methods. It was found that for all methods adopted in the bearing capacity estimation, the undrained bearing capacity increases with the strength density. As a result, the failure mechanism becomes shallower and narrower as the undrained shear strength increases with depth. Comparing the results obtained by the applied methods, the maximum bearing capacity is rendered by the limit equilibrium (assuming Terzaghi failure mechanism), resulting as an unsafe solution. On the contrary, the minimum bearing capacity is yielded by the stress characteristic method, as the most conservative and applicable solution.